Pengaruh Kegiatan Modul Nusantara Terhadap Mahasiswa Outbound Universitas Muhammadiyah Bulukumba Dalam Program Pertukaran Mahasiswa Merdeka - Ainun Awalia; Achmad, Ilmar Andi; Emirati (Learning Community : Jurnal Pendidikan Luar Sekolah, 2025)
This study aims to determine the effect of Nusantara Module activities on Outbound Students of Muhammadiyah Bulukumba University in the Batch 3 Merdeka Student Exchange Program (PMM 3) at Medan State University. The focus of this research is the multicultural experience of students on the four core activities of the archipelago module, namely diversity activities, inspiration activities, reflection activities, and social contribution activities. This research uses a qualitative descriptive approach. Data collection techniques used observation, interview, and documentation techniques. The data analysis used was qualitative data analysis with data reduction steps, data presentation, and conclusion drawing. The results showed that the archipelago module activities consisting of diversity activities, inspiration activities, reflection activities, and social contribution activities, proved to be an effective initiative in increasing students' multicultural experience, enriching students' understanding of Indonesia's cultural diversity, and strengthening students' tolerance and social responsibility.